SINERGI INOVASI, MODAL BUDAYA DAN PARTISIPASI MASYARAKAT DALAM MENCIPTAKAN KESEJAHTERAAN UMKM - I Made Sara; Made Setini; I Gusti Lanang Putu Tantra (EKUITAS (Jurnal Ekonomi dan Keuangan), 2022)
The happiness level of MSME actors determines the regional economy. Small business innovation is the driving force behind MSMEs' happiness and business continuity. Business units classified as micro, small and medium enterprises (MSMEs) are the locomotives of the regional and national economies. This study aimed to analyze the influence of cultural capital and community involvement on the well-being of MSMEs either directly or through MSME innovation. This study was conducted on MSME agents. Data was collected through questionnaires from 350 MSME agents and 150 MSME agents, and data analysis was performed using the SEM PLS. The study results indicate that cultural capital and community involvement have a positive and significant impact on the innovations undertaken by MSMEs. The cultural capital and innovation of MSMEs have a positive and significant effect on the happiness of MSMEs. In contrast, the role of community participation has an insignificant effect on the happiness of MSMEs. MSME innovation controls the impact of cultural capital on MSME welfare with partial mediation, and MSME innovation controls the impact of public engagement on MSME welfare with complete mediation.